Antimicrobial efficacy of sodium hypochlorite and hyper-pure chlorine dioxide in the depth of dentin tubules in vitro - Enikő Vasziné Szabó; Brigitta Huszta; Melinda Polyák; Kasidid Ruksakiet; Róbert Bernáth; Ágoston Ghidán; Ágnes Csáki; Milia Kostadinova; Elek Dinya; János Vág; Zsolt M. Lohinai (BMC, 2023)
Abstract Objectives The study aimed to compare the antibacterial effect of a novel disinfectant, hyper-pure chlorine dioxide (hClO2) to sodium hypochlorite (NaOCl) in various depths of dentin tubules. Materials and methods The distal root of the extracted lower molars was infected artificially with Enterococcus faecalis. The control group was rinsed with saline, and the test groups were irrigated with either 5% NaOCl or 0.12% hClO2. The longitudinally split teeth were stained by viability stain. The coronal third of the root was scanned with a confocal laser scanning microscope. The fluorescent intensities were measured, and the percentage of dead bacteria was calculated at depths up to 950 μm along the dentin tubules. The effect of penetration depth, irrigants, and their interaction on antimicrobial efficacy was determined by the linear mixed model. Results The percentage of dead bacteria was higher both in the NaOCl (45.1 ± 2.3%, p < 0.01) and in the hClO2 (44.6 ± 3.8%, p < 0.01) irrigant groups compared to saline (23 ± 4.5%); however, there was no difference between them. The percentage of killed bacteria was not correlated with the depths in any group (p = 0.633). Conclusions Our results suggest that the functional penetration depth of NaOCl is at least 2-3 times more than published to date. There is no difference in disinfection effectiveness along the dentin tubules between NaOCl and hClO2 until at least the measured 950 μm. However, both were only able to eradicate the intratubular bacteria partially. Clinical relevance Hyper-pure ClO2 could be used as an alternative or final adjuvant irrigant in endodontic treatment.